A recurrent de novo mutation in ACTG1 causes isolated ocular coloboma. Issue 8 (6th June 2017) - Rainger, Joe; Williamson, Kathleen A; Soares, Dinesh C; Truch, Julia; Kurian, Dominic; Gillessen‐Kaesbach, Gabriele; Seawright, Anne; Prendergast, James; Halachev, Mihail; Wheeler, Ann; McTeir, Lynn; Gill, Andrew C; et al.
Abstract : Ocular coloboma (OC) is a defect in optic fissure closure and a common cause of severe congenital visual impairment. We identified de novo mutations in 10 different genes in eight unrelated individuals with isolated OC, using whole exome sequencing. Three of these genes encoded proteins associated with actin cytoskeleton dynamics and the mutations impacted on normal actin function. Only mutations in ACTG1 were recurrent among a larger cohort upon targeted re‐sequencing, suggesting that to accurately determine all of the disease‐accolated loci for this important eye malformation, sequencing of many more families is required. Abstract: Ocular coloboma (OC) is a defect in optic fissure closure and is a common cause of severe congenital visual impairment. Bilateral OC is primarily genetically determined and shows marked locus heterogeneity. Whole‐exome sequencing (WES) was used to analyze 12 trios (child affected with OC and both unaffected parents). This identified de novo mutations in 10 different genes in eight probands. Three of these genes encoded proteins associated with actin cytoskeleton dynamics: ACTG1, TWF1, and LCP1 . Proband‐only WES identified a second unrelated individual with isolated OC carrying the same ACTG1 allele, encoding p.(Pro70Leu). Both individuals have normal neurodevelopment with no extra‐ocular signs of Baraitser–Winter syndrome. We found this mutant protein to be incapable of incorporation into F‐actin. The LCP1 and TWF1 variants each resulted in only minor disturbance of actin interactions, and no further plausibly causative variants were identified in these genes on resequencing 380 unrelated individuals with OC.